Changes in fears and worries related to COVID-19 during the pandemic among current employees in Japan: a 5-month longitudinal study. (September 2021) - Hidaka, Y.; Sasaki, N.; Imamura, K.; Tsuno, K.; Kuroda, R.; Kawakami, N.
Abstract: Objectives: This study investigates and describes the time course of fears and worries about COVID-19 among current employees during this outbreak. Study design: This was a longitudinal study. Methods: This study was a part of the Employee Cohort Study in Japan. The study comprised 4120 individuals from February 2019. A baseline survey in March 2020, a 2-month follow-up survey in May 2020, and a 5-month follow-up survey in August 2020 were conducted. Questions surveyed respondents' global fear and worry and six items related to COVID-19. A mixed model for repeated measures of an analysis of variance was used. Results: A total of 1421 respondents completed the baseline survey. At 2- and 5-month follow-ups, 1032 and 1181 respondents completed surveys, respectively. Of those, 64 and 33 individuals who were temporarily laid off or on leave were recorded as missing values. Global fear and worry about COVID-19 significantly increased from March to August 2020. Fears of personal or family infection, limiting one's activities and national and local government policies also significantly increased with time. In contrast, fears of lack of knowledge and difficulty of obtaining hygiene products significantly decreased. Conclusion: To conduct efficient risk communication during a pandemic, knowing the concerns of the populace, providing correct information and a sufficient supply of products, and setting clear guidelines are essential.